Towards a systematic analysis of human short-chain dehydrogenases/reductases (SDR): Ligand identification and structure–activity relationships. (5th June 2015) - Bhatia, Chitra; Oerum, Stephanie; Bray, James; Kavanagh, Kathryn L.; Shafqat, Naeem; Yue, Wyatt; Oppermann, Udo
Highlights: Differential scanning fluorimetry (DSF) facilitates rapid ligand identification. DSF is used to identify ligand specificities for human short-chain dehydrogenase/reductases. X-ray crystallography confirms identified DSF hits. Abstract: Short-chain dehydrogenases/reductases (SDRs) constitute a large, functionally diverse branch of enzymes within the class of NAD(P)(H) dependent oxidoreductases. In humans, over 80 genes have been identified with distinct metabolic roles in carbohydrate, amino acid, lipid, retinoid and steroid hormone metabolism, frequently associated with inherited genetic defects. Besides metabolic functions, a subset of atypical SDR proteins appears to play critical roles in adapting to redox status or RNA processing, and thereby controlling metabolic pathways. Here we present an update on the human SDR superfamily and a ligand identification strategy using differential scanning fluorimetry (DSF) with a focused library of oxidoreductase and metabolic ligands to identify substrate classes and inhibitor chemotypes. This method is applicable to investigate structure–activity relationships of oxidoreductases and ultimately to better understand their physiological roles.